Pengaruh Customer Relationship Management (CRM), Customer Value serta Kepercayaan terhadap Loyalitas Kepuasan Nasabah - Imam Fatoni; Nyoman Sockarini (COSTING : Journal of Economic, Business and Accounting, 2019)
Customer satisfaction can be a determining factor in increasing customer purchases of a product and service. This study aims to determine the effect of variable customer relationship management, customer value, trust and customer satisfaction on customer loyalty PT.Adira Finance Jember. The data used in this study is primary data. Data processing method uses path analysis method with the help of SPSS 24 analysis tools.. The results showed that the variable customer relationship management, customer value, trust and customer satisfaction influence the customer loyalty of PT.Adira Finance Jember either directly or indirectly Keywords: CRM, Customer Value, Trust, Customer Satisfaction, Customer Loyalty